Ticagrelor versus prasugrel in patients with acute myocardial infarction. (1st December 2021) - Park, Sangwoo; Kim, Yong-Giun; Ann, Soe Hee; Park, Hyun Woo; Suh, Jon; Roh, Jae-Hyung; Cho, Young-Rak; Han, Seungbong; Park, Gyung-Min
Abstract: Background: Ticagrelor and prasugrel are the mainstay of antithrombotic therapy for patients with acute myocardial infarction (MI). However, direct comparative data on clinical outcomes of potent P2Y12 inhibitors are limited, especially in East Asian populations. We aimed to evaluate the effect of ticagrelor versus prasugrel on clinical outcomes in patients with acute MI. Methods: From the Korean nationwide National Health Insurance database, 10, 797 patients with acute MI who received either ticagrelor or prasugrel in combination with aspirin after percutaneous coronary intervention (PCI) were enrolled. The primary outcome was net clinical benefit, defined as a composite of death, MI, stroke, or major bleeding. Secondary outcomes included the individual components of the primary outcome as effectiveness and safety measures. Results: Among 10, 797 patients, 9591 (88.8%) received ticagrelor and 1206 (11.2%) received prasugrel. During a median follow-up of 1.8 years, the primary outcome occurred in 1051 (16.6%) and 131 (14.4%) patients in the ticagrelor and prasugrel groups, respectively. In the propensity score matched cohort ( n  = 5979), the risk for the primary outcome was similar between the two groups (hazard ratio [HR] 0.949 for prasugrel; 95% confidence interval [CI]: 0.780–1.154). The risks for the composite of death, MI, or stroke (HR 0.938; 95% CI: 0.752–1.169) and major bleeding (HR 1.022; 95% CI: 0.709–1.472) were also comparable. Conclusions: In patients with acute MI undergoing PCI, ticagrelor and prasugrel appeared to have similar net clinical benefits. The risks for death, MI, or stroke and major bleeding were not significantly different between the two groups. Highlights: Clinical impact of ticagrelor and prasugrel was evaluated in a nationwide cohort. Net clinical benefit was comparable between ticagrelor and prasugrel in East Asian. The risk for the composite of death, MI, or stroke was similar between groups. The risk for major bleeding was also similar between groups.